Management science in banking - Cohen, Kalman J.; Gibson, Stephen E. (Boston ; New York : Warren, Gorham & Lamont, 1978)
The book deals on increasing the readers knowledge of current attempts by management science researchers to apply scientific techniques to banking problems
Includes bibliographical references and index.
ucj 16/01/2019
Loans
Keywords: Bank management